Immuno-localization of glucose transporter 4 in healthy human gingiva - Suresh Ranga Rao; Sandhya Sundaram; Vamsi Lavu (Wolters Kluwer Medknow Publications, 2012)
Background: The gingiva has been shown to be a target tissue for several hormones. Insulin induces uptake of glucose in the peripheral tissues by upregulating the Glucose transporter 4 expression. Little information is available on the expression of Glucose transporter 4 in human gingiva. Aim: In this regard, a pilot study was performed with the aim of determining the distribution pattern of Glucose transporter 4 in healthy human gingiva. Materials and Methods: Immuno-histochemistry was performed on 10 mounted sections of healthy human gingiva with the primary antibody Glucose Transporter 4 (GLUT 4). Appropriate positive and negative controls were used. Results: Glucose transporter 4 expression was observed in the basal and suprabasal layers of the gingival epithelium and fibroblasts of the gingival connective tissue. Conclusion: This may be the first study to demonstrate the expression of GLUT 4 in the healthy human gingiva. The results of this study raise the possibility that gingiva may serve as a target tissue for insulin action.